The role of viruses in the cancerogenesis - Chojnicki, Michał; Pawlaczyk, Mariola; Helak-Łapaj, Celina; Żurawski, Jakub; Wiktorowicz, Krzysztof (Journal of Medical Science, 2014)
It is estimated that seven key viruses such as Hepatitis B virus (HBV), Hepatitis C virus (HCV), Human T-lymphotropic virus (HTLV), Human papilloma viruses (HPV), Kaposi’s sarcoma-associated herpes-virus (KSHV), Epstein-Barr virus (EBV) and Merkel cell polyomavirus (MCV), are responsible for about 11% of cancers all over the world. Viruses however are not only associated with cancerogenesis process. Scientific researches from recent years emphasize the possible use of the microorganisms as antitumor therapy. Oncoviruses, also defined as tumor viruses cause cancers whereas oncolytic viruses infect the host’s cancer cells leading to destruction of tumor and due to that they are described as cancer killing viruses. It offers the potential application of viral infections to the cancer therapy.